Implementasi Complementary Filter Pada Perancangan Alat Bantu Makan Penderita Parkinson - Indra Dwi Cahyo; Wijaya Kurniawan; Mochammad Hannats Hanafi Ichsan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Parkinson are diseases which found at the early age of 30 yerars.with unsynergyness of motoric nerve parkinson's holding spoonmake eating become difficult.This research design eating tool with stability using complementary filter. This research use MPU6050 sensor, stepper motor 28BYJ-485V and Arduino Nano. The data of shaking of the hands can be captured with MPU6050. Stepper motor used for stabilize spoon because of the parkinson's tremor. Arduino nano serves as data processing for whole program and complementary filter equation to reduce noise from MPU6050 sensor. This research found that complementary filter can reduce angle error of stepper motor because of MPU6050 reading up to 4.34 degree for pitch and 3.07 degree for roll. Not only that this research found that complementary filter usage in this system can make MPU6050 reading for stepper motor movement become more stable and the movement of pitch and roll become moresynergystic.